Spatiotemporal dynamics of Brucella immune evasion across infection stages - Su, Yu; Zhang, Lihui; Liu, Ruihua; Sa, Rina; Zheng, Lanbing (Frontiers in Immunology, 2026)
Brucella, a major zoonotic pathogen, poses a significant threat to global public health and causes substantial economic losses in the livestock industry. It employs diverse and sophisticated immune evasion strategies to circumvent host surveillance, establishing and maintaining chronic infections that are difficult to treat and prone to relapse. While previous reviews have catalogued individual virulence factors—such as the VirB type IV secretion system—and their actions on pathways like TLR4 signaling, most analyses focus on isolated stages or mechanisms, overlooking the integrated, dynamic regulation spanning the entire infection course. A systematic framework explaining how Brucella modulates host immunity through multi-stage, multidimensional evasion is still lacking. This review synthesizes research from the past decade to delineate the Brucella immune-evasion network across four distinct stages: colonization, latency, acute disease, and chronic persistence. We propose a Spatiotemporal Dynamic Immune Evasion Model that unifies these processes, offering novel insights into the immunological basis of chronic brucellosis and providing a foundation for developing stage-specific therapeutics and next-generation vaccines with strong translational potential.